Lack of iron, zinc, and vitamins as a contributor to the etiology of atopic diseases - Peroni, Diego G.; Hufnagl, Karin; Comberiati, Pasquale; Roth-Walter, Franziska (Frontiers in Nutrition, 2023)
Micronutrional deficiencies are common in atopic children suffering from atopic dermatitis, food allergy, rhinitis and asthma. A lack of iron, in particular, may impact immune activation with prolonged deficiencies of iron, zinc, vitamin A and Vitamin D associated with a Th2 signature, maturation of macrophages and dendritic cells and the generation of IgE antibodies. In contrast, the sufficiency of these micronutrients establishes immune resilience, promotion of regulatory cells and tolerance induction. As micronutritional deficiencies mimic an infection, the body’s innate response is to limit access to these nutrients and also impede their dietary uptake. Here we summarize our current understanding of the physiological function of iron, zinc, and vitamin A and D in relation to immune cells and the clinical consequences of deficiencies in these important nutrients, especially in the perinatal period. Improved dietary uptake of iron is achieved by Vitamin C, Vitamin A and whey compounds, whereas zinc bioavailability improves through citrates and proteins. The addition of oil is essential for the dietary uptake of beta-carotenes and Vitamin D. As for Vitamin D, the major source comes via sun exposure and only a small amount is consumed via diet, which should be factored into clinical nutritional studies. We summarize the prevalence of micronutrional deficiencies of iron, zinc, and vitamins in the pediatric population as well as nutritional intervention studies on atopic diseases with whole food, food components and micronutrients. Dietary uptake via the lymphatic route seems promising and is associated with a lower atopy risk and symptom amelioration. This review provides useful information for clinical studies and concludes/emphasizes that a healthy, varied diet containing dairy products, fish, nuts, fruits and vegetables as well as supplementing foods or supplementation with micronutrients as needed, is essential to combat the atopic march.